Determination of the Optimal Cutoff Value of Triglyceride That Corresponds to Fasting Levels in Chinese Subjects With Marked Hypertriglyceridemia - Guo, Li-Ling; Zhu, Li-Yuan; Xu, Jin; Xie, Ying-Ying; Xiang, Qun-Yan; Jiang, Zhe-Yi; Tan, Yang-Rong; Liu, Ling (Frontiers in Cardiovascular Medicine, 2021)
The level of triglyceride (TG) ≥ 2. 3 mmol/L is suggestive of marked hypertriglyceridemia (HTG) and requires treatment with a triglyceride-lowering agent in high-risk and very high-risk patients as recommended by the 2019 ESC/EAS guidelines for the management of dyslipidemia. However, the optimal cutoff value required to diagnose non-fasting HTG that corresponds to the fasting goal level of 2.3 mmol/L in Chinese subjects is unknown. This study enrolled 602 cardiology inpatients. Blood lipid levels, including calculated non-high-density lipoprotein cholesterol (non-HDL-C) and remnant cholesterol (RC), were measured at 0, 2, and 4 h after a daily Chinese breakfast. Of these, 482 inpatients had TG levels of <2.3 mmol/L (CON group) and 120 inpatients had TG levels of ≥2.3 mmol/L (HTG group). Receiver operating characteristic (ROC) curve analysis was used to determine the cutoff values for postprandial HTG that corresponded to a target fasting level of 2.3 mmol/L. Marked hypertriglyceridemia (≥2.3 mmol/L) was found in 120 (19.9%) patients in this study population. The levels of non-fasting TG and RC increased significantly in both groups and reached the peak at 4 h after a daily meal, especially in the HTG group (p < 0.05). The optimal cutoff value of TG at 4 h, which corresponds to fasting TG of ≥2.3 mmol/L, that can be used to predict HTG, was 2.66 mmol/L. According to the new non-fasting cutoff value, the incidence of non-fasting HTG is close to its fasting level. In summary, this is the first study to determine the non-fasting cutoff value that corresponds to a fasting TG of ≥2.3 mmol/L in Chinese patients. Additionally, 2.66 mmol/l at 4 h after a daily meal could be an appropriate cutoff value that can be used to detect non-fasting marked HTG in Chinese subjects.